Risk aversion, prospect theory, and strategic risk in law enforcement: Evidence from an antitrust experiment - Maria Bigoni; Sven-Olof Fridolfsson; Chloé Le Coq; Giancorlo Spagnolo (Stockholm School of Economics, The Economic Research Institute (EFI), 2008)
In this paper we investigate the effects of risk preferences and attitudes towards risk on optimal antitrust enforcement policies. First, we observe that risk aversion is negatively correlated with players' proclivity to form a cartel, and that increasing the level of fines while reducing the probability of detection enhance deterrence. This confirms that the design of an optimal law enforcement scheme must keep risk attitudes into account, as suggested by Polinsky and Shavell. We also notice that players' propensity towards communication drops right after detection even if the collusive agreement was successful, and it declines as the sum of the fines paid by a subject increases. This effect could be explained by availability heuristic - a cognitive bias, where people's perception of a risk is based on its vividness and emotional impact rather than on its actual probability. Our results also confirm the crucial role of strategic risk considerations (analogous to risk dominance for one shot games) in determining the effects of leniency programs. Indeed, we show that the effectiveness of leniency programs in deterring cartels is mostly due to the increased risk of a cartel member being cheated upon when entering a collusive agreement, while the risk of a cartel being detected by an autonomous investigation of the Authority seems to play a less important role.
Keywords: C92; D43; D81; 330; Collusion; Leniency; Experiments; Risk Aversion; Availability Heuristic; Strategic Risk; Risikoaversion; Prospect Theory; Rechtsdurchsetzung; Kartell; Test; Theorie